Mams, moms, mums: lone mothers' accounts of management strategies. Issue 4 (8th August 2022) - Leonard, Madeleine; Kelly, Grace
ABSTRACT: Management strategies are typically associated with economic goals and neglect how women's daily lives incorporate non-economic goals. To illustrate this point, the paper draws on the narratives of 32 lone mothers who have to confront various constraints in terms of how they manage the resources at their disposal paying particular attention to how their subjective accounts impact on their conceptions of the mothering role. Mothers continually strive to make decisions based on how they consider, negotiate and balance economic and non-economic responsibilities. Based on the women's narratives, the women were categorised into three core groups: MAMs (mothers actively managing), MOMs (mothers only managing) and MUMs (mothers under managing). This typology is used to identify and explore factors that enable women to counter constraints, intensify agency and thereby enhance their ability to make decisions they believe are right for them and their families. In the process, the women demonstrate how they perceive motherhood and how their subjective evaluations of their ability/inability to match their expectations are fundamental to their sense of well-being in terms of managing everyday life.